An Efficient Key Management Scheme Based on ECC and AVL Tree for Large Scale Wireless Sensor Networks - Zhongyuan Qin; Xinshuai Zhang; Kerong Feng; Qunfang Zhang; Jie Huang (International Journal of Distributed Sensor Networks)
With the wide adoption of wireless sensor network (WSN), security problems emerge as a challenging issue because of the limited computational power and energy of the sensor nodes. Furthermore, the deployment of WSN in the hostile area with a large number of nodes also poses a threat. In this paper, we proposed a new efficient key management scheme based on Elliptic Curve Cryptography (ECC) and AVL tree for large scale WSNs. In our scheme the Elliptic Curve Paillier Encryption (ECPE) cryptography is adopted for communication and the AVL tree is used to store the neighbors' ID and public key. The number of keys used in our scheme is smaller than the proposed schemes as we store these keys using AVL tree to shorten the search time. Regular key updates are also designed to further improve the security of the whole network. Our scheme has a good scalability where the node addition and deletion are supported. Experimental results and analysis show our scheme can significantly reduce the energy consumed by the node and reduce the memory and computational overhead.